The Effect of Transparency and Accountability on Muzaki Loyalty through Muzaki Satisfaction as an Intervening Variable at the Amil Zakat Institution (LAZ) in Indonesia: Transparency, accountability, muzaki’s satisfaction, muzaki’s loyalty, amil zakat institutions - Salman, Kautsar Riza; Anggraini, Rahimdiawati Mila (Journal of Finance and Islamic Banking, 2022)
The primary item that needs to be discussed and pursued is the increasing number of people who pay zakat (muzaki). This is meant to maximize the role of zakat in reducing poverty in Indonesia. This study used muzaki satisfaction as an intervening variable to examine the influence of transparency and accountability on muzaki loyalty. Muzaki of the Amil Zakat Institute, Nurul Hayat Tuban, was the focus of this study. In this study, 48 people were gathered through an offline distribution in the Tuban district. SPSS version 25 was used to analyse the questionnaire responses. This study indicates that Muzaki’s satisfaction is significantly influenced by direct (partial) transparency. Accountability does not influence muzaki satisfaction when applied directly. Transparency does not influence muzaki loyalty in the short-term. Direct responsibility does not influence muzakiloyalty. Muzaki’s satisfaction directly influences loyalty. Muzaki satisfaction can improve muzaki loyalty by mediating (intervening) transparency. Furthermore, muzaki satisfaction is incapable of mediating (intervening) accountability in muzakiloyalty.